2013
DOI: 10.1186/1476-7120-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Peak systolic velocity using color-coded tissue Doppler imaging, a strong and independent predictor of outcome in acute coronary syndrome patients

Abstract: BackgroundTraditional echocardiographic methods like left ventricular ejection fraction(EF) and wall motion scoring (WMS) and new methods like speckle tracking (ST) based 2D strain carry important prognostic information in acute coronary syndrome (ACS) patients. Parameters from tissue Doppler imaging (TDI), with its high time resolution, may further increase the prognostic value. Peak systolic velocity (PSV) of the basal segments of the left ventricle from TDI is a robust and user independent parameter. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Changes in macrovascular flow characteristics that may be associated with increased haematocrit are also potentially important. Both end diastolic and peak systolic velocities have been associated with atherogenesis [72][73][74][75][76]. Our research group found that lower peak systolic velocity, based on ultrasound measurements in the carotid artery, was associated with coronary heart disease [72].…”
Section: Association Between Elevated Haematocrit and T2dmmentioning
confidence: 73%
“…Changes in macrovascular flow characteristics that may be associated with increased haematocrit are also potentially important. Both end diastolic and peak systolic velocities have been associated with atherogenesis [72][73][74][75][76]. Our research group found that lower peak systolic velocity, based on ultrasound measurements in the carotid artery, was associated with coronary heart disease [72].…”
Section: Association Between Elevated Haematocrit and T2dmmentioning
confidence: 73%
“…Pairwise comparisons for LV S', V max LVOT , and stroke volume index at peak exercise revealed that while there were no differences between HIIT and MICT interventions, the exercise interventions were superior to nutrition advice only for eliciting improvements in these outcomes ( Figure 3 B & D). Importantly, the estimated mean differences between the exercise and nutrition groups for peak exercising LV S' were clinically significant 11 . The exercise interventions increased recovery systolic cardiac function (LV S') compared to the nutrition only intervention while the HIIT group exhibited greater improvements in recovery diastolic cardiac function (LV e') compared to the nutrition only group (Supplemental Table 3).…”
Section: Peak Exercise and Recovery Cardiac Functionmentioning
confidence: 88%
“…For calculation of sample size, the clinically meaningful difference in peak systolic tissue velocity was set to 1cm/s with a standard deviation of 0.9cm/s 11 An intention-to-treat (HIIT=33; MICT=32; nutrition=34) and per protocol analysis (HIIT=17; MICT=24; nutrition=21) was conducted for the LMM. All available data were…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations